DEVELOPMENT INITIATIVE OF MANUFACTURING AND SERVICE CLUSTERS IN THE REPUBLIC OF SERBIA CORRIDOR 10 ZONE - Nikezić, Srđan; Bataveljić, Dragan; Matić, Milutin (Economics of Agriculture, 2012)
In this paper, the authors strive to indicate some great possibilities for further development of rural areas in the wider zone of Corridor 10 in the Republic of Serbia. The significance of manufacturing and service clusters, networks and co-operations formed in rural areas, creating a large number of small and medium enterprises as a manner of running the entire industry through accelerated development of entrepreneurial initiative, is also stressed. A special kind of attention paid to the development of SMEs is a document from June 2008, adopted by the EU under the title: A Small Business Act for Europe, with established principles and actions for operating in the section of small and medium-sized enterprises in the EU. The aspect of joining agricultural production and processing with service industry that could be implemented along the Corridor 10 is dominant in this paper. Clusters are networks of companies and institutions that complement each other creating cooperative supply chains, where food-service supply chains are especially stressed in the wider rural area of Corridor 10 with obligatory appliance of the European Alert System for Food and Feed (RASFF) standard, reaching over 7,000 notifcations. Those notifcations are related to potentially dangerous food or animal feeding and are issued by RASFF system founded by the European Commission.